UJI AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL KULIT PISANG RAJA (Musa paradisiaca L.) SEBAGAI BAHAN BAKU PEMBUATAN ICE CREAM DENGAN METODE FERRIC REDUCING ANTIOXIDANT POWER - Abidin, Zainal; Aminah, Aminah; Ummum, Andi (PHARMACY UMI JOURNAL SYSTEM, 2024)
Antioxidants are defined as inhibitors that work to inhibit oxidation by reacting with reactive free radicals to form stable unreactive free radicals. Antioxidants are substances that can delay, slow down and prevent the oxidation process or neutralize free radicals. Plantain peel contains several metabolite compounds that have the potential to have antioxidant activity such as saponins, polyphenols and tannins, flavonoids and terpenoids. Banana peel extract has high antioxidant activity. The methanol extract of banana peels was higher in total flavonoids and phenolics compared to the n-hexane extract of banana peels. The aim of this research was to test the antioxidant activity of the ethanol extract of plantain peel using the FRAP (Ferrc Reduxing Antioxidant Power) method. The extraction method for plantain peel uses the maceration method with 96% ethanol solvent. The ethanol extract of plantain peel was then added with several FRAP reagents then measured using a UV-Vis spectrophotometer at a wavelength of 720 nm with quercetin as a comparison and the results of the quercetin test obtained a linearity equation y = 0.0207x + 0.0114 with a correlation coefficient value of r = 0.9904. The results showed that the ethanol extract of plantain peel had antioxidant activity of 26.5828 mgQE/g extract.